Pengaruh Efektivitas Penggunaan Mesin Self Check-In Terhadap Kepuasan Penumpang Maskapai Citilink Di Yogyakarta International Airport - Adelia Irvana Bintang; Teguh Ariebowo (STIKes Ibnu Sina Ajibarang, 2024)
PT Angkasa Pura I provided operational support to better the passenger time with self check-in. Self check-in is a service system that allows passengers for self check to reduce queues Check-In Counter. The study aims to understand significantly the impact and influence of the effectiveness of the use of the self check-in machine on the passenger satisfaction of the citilink airline at Yogyakarta International Airport. The research is a quantitative using primary data of the survey (questionnaire) and observation in its collection. The sample in this research uses a nonsampling technique type adhesive with the slovin formula gets 100 respondents. Data analysis techniques for analyzing this research are instrument tests, classic assumptions test, simple linear regression analysis. The results of the research suggest that the effectiveness of the use of the self check-in engine has significantly affected the passenger satisfaction greater than t table (21.756 > 1.660), which means h0 was rejected and ha received. The effectiveness of the use of the self check-in machine to affect passenger complacency by 82.8% while the remaining 172% are affected by variables or other factors not used in the research.